Efisiensi Operasional dan Akuntansi Hotel melalui Magang Mahasiswa pada Royal Avila - Isna, Isnawati; Mas Prapti Wagi Swari, Ni Luh; Baturaja, Susan; Isnaini, Zuhrotul (https://jurnal.fe.unram.ac.id/index.php/abdimas/about/privacy, 2025)
The student internship program serves as a strategic medium for integrating academic learning with practical experience in an industrial setting. The internship was carried out over a four-month period at Royal Avila Boutique Resort, with responsibilities focused on operational efficiency and hotel accounting, particularly in transaction input, inventory management, and audit control. The implementation method was both collaborative and participatory. Activities were conducted using the Visual Hotel Program (VHP) system and applied an adaptive approach through observation, technical training, and direct involvement in daily work processes. Interns were actively involved in entering PR, PO, SR, and IDT documents, AR and AP journal entries, and assisting the income auditor in reviewing daily revenue data. Inventory procedures that previously required more time were completed approximately three hours earlier. The involvement of student interns contributed to time efficiency, a 5–8% reduction in recording errors, and the optimization of finance staff workload. This experience demonstrates that internship programs not only benefit student development, but also provide meaningful contributions in supporting operational tasks within the industry